2015
DOI: 10.1016/j.actao.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Plant community assembly at small scales: Spatial vs. environmental factors in a European grassland

Abstract: 24Dispersal limitation and environmental conditions are crucial drivers of plant species 25 distribution and establishment. As these factors operate at different spatial scales, we asked: Do 26 the environmental factors known to determine community assembly at broad scales operate at 27 fine scales (few meters)? How much do these factors account for community variation at fine 28 scales? In which way do biotic and abiotic interactions drive changes in species composition? 29We surveyed the plant community with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 50 publications
1
11
1
2
Order By: Relevance
“…ex J. Presl & C. Presl., Armeria elongata Hoff., and Rumex acetosella L. (Horn et al, 2015), which have been frequently reported for dry grasslands in north eastern Germany (Hensen, 1997).…”
Section: The Study Systemmentioning
confidence: 69%
See 1 more Smart Citation
“…ex J. Presl & C. Presl., Armeria elongata Hoff., and Rumex acetosella L. (Horn et al, 2015), which have been frequently reported for dry grasslands in north eastern Germany (Hensen, 1997).…”
Section: The Study Systemmentioning
confidence: 69%
“…Our experimental microcosms were designed to recreate conditions found in a natural grassland located near the town of Mallnow, Lebus (Brandenburg, Germany, 52°127.77′N, 14°129.349′E) (referred as the "Mallnow Grassland" throughout this study). Specifically, this study is based on the vegetation occurring in a 15 × 15 m plot within this grassland that was used in previous studies in our laboratory (Horn, Caruso, Verbruggen, Rillig, & Hempel, 2014;Horn et al, 2015). Within the plot, there is a strong gradient in soil texture from loamy to sandy soil along a hillside.…”
Section: The Study Systemmentioning
confidence: 99%
“…Other studies have used null models to detect patterns of plant species assembly in invasion processes, particularly comparing between invaded and uninvaded areas along environmental gradients (Cornwell and Ackerly, 2009;Jansen et al, 2011;Santoro et al, 2012;Horn et al, 2015). However, as far as we know, no previous research has focused on the spatial patterns of a whole community of plant species that undertook transcontinental naturalization by comparing species assembly between the source area and the invaded region.…”
Section: Introductionmentioning
confidence: 98%
“…Other than occasional grazing, implemented for conservation purposes, disturbance levels in the reserve are low. We focused our harvests on three hills that exhibited gradients in soil texture (the top of the hills were sandy-loamy whereas downhill the soil was sandy -see Horn et al 2015) with pronounced implications on plant composition and nutrient availability. On each of the three hills we marked three square macroplots with sides that varied from 12 to 15m.…”
Section: Experimental Designmentioning
confidence: 99%